Kabuki syndrome stem cell models reveal locus specificity of histone methyltransferase 2D (KMT2D/MLL4). Issue 21 (28th May 2022) - Jefri, Malvin; Zhang, Xin; Stumpf, Patrick S; Zhang, Li; Peng, Huashan; Hettige, Nuwan; Theroux, Jean-Francois; Aouabed, Zahia; Wilson, Khadija; Deshmukh, Shriya; Antonyan, Lilit; Ni, Anjie; et al.
Abstract: Kabuki syndrome is frequently caused by loss-of-function mutations in one allele of histone 3 lysine 4 (H3K4) methyltransferase KMT2D and is associated with problems in neurological, immunological and skeletal system development. We generated heterozygous KMT2D knockout and Kabuki patient-derived cell models to investigate the role of reduced dosage of KMT2D in stem cells. We discovered chromosomal locus-specific alterations in gene expression, specifically a 110 Kb region containing Synaptotagmin 3 ( SYT3 ), C-Type Lectin Domain Containing 11A ( CLEC11A ), Chromosome 19 Open Reading Frame 81 ( C19ORF81 ) and SH3 And Multiple Ankyrin Repeat Domains 1 ( SHANK1 ), suggesting locus-specific targeting of KMT2D. Using whole genome histone methylation mapping, we confirmed locus-specific changes in H3K4 methylation patterning coincident with regional decreases in gene expression in Kabuki cell models. Significantly reduced H3K4 peaks aligned with regions of stem cell maps of H3K27 and H3K4 methylation suggesting KMT2D haploinsufficiency impact bivalent enhancers in stem cells. Preparing the genome for subsequent differentiation cues may be of significant importance for Kabuki-related genes. This work provides a new insight into the mechanism of action of an important gene in bone and brain development and may increase our understanding of a specific function of a human disease-relevant H3K4 methyltransferase family member.